2015
DOI: 10.1111/jph.12384
|View full text |Cite
|
Sign up to set email alerts
|

New Records of Lasiodiplodia theobromae in Seeds of Tetrapleura tetraptera from Nigeria and Fruit of Cocos nucifera From Mexico

Abstract: The cosmopolitan warm‐climate plant pathogen Lasiodiplodia theobromae was isolated from two sources: Seeds of Tetrapleura tetraptera from Nigeria and fruits of Cocos nucifera from Mexico; the former instance is novel for host, the latter a novel geographic record for infection of coconut fruits. Per cent germination of T. tetraptera seeds was negatively and significantly correlated with per cent infection by the fungus. Repeated tests with isolates from both coconut and Tetrapleura confirmed pathogenicity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Endophytic Fusarium strains have previously been found to promote germination and seedling growth of an Indonesian peatland grass ( Tamura et al, 2008 ) and germination of orchid seeds ( Bayman and Otero, 2007 ). In addition to the aforementioned roles of L. theobromae in tropical fruit tree diseases, it has also been implicated in seed rot, for instance of slash pine ( Cilliers et al, 1993 ), and to cause reduced germination rates in aridan and coconut seeds ( Dugan et al, 2016 ). The role of seedborne L. theobromae on germination may be more nuanced, however, as it has been found to produce fatty acid esters, which can alternately inhibit and promote tobacco seed germination and seedling growth ( Uranga et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic Fusarium strains have previously been found to promote germination and seedling growth of an Indonesian peatland grass ( Tamura et al, 2008 ) and germination of orchid seeds ( Bayman and Otero, 2007 ). In addition to the aforementioned roles of L. theobromae in tropical fruit tree diseases, it has also been implicated in seed rot, for instance of slash pine ( Cilliers et al, 1993 ), and to cause reduced germination rates in aridan and coconut seeds ( Dugan et al, 2016 ). The role of seedborne L. theobromae on germination may be more nuanced, however, as it has been found to produce fatty acid esters, which can alternately inhibit and promote tobacco seed germination and seedling growth ( Uranga et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…En algunos casos ha sido posible asociar síntomas con la especie del patógeno debido a ciertas características como la presencia de anillos en las lesiones (Tian et al, 2018). Los síntomas asociados a estos hongos son: cancro en ramas y tronco, declinamiento, gomosis, muerte descendente de ramas, necrosis en hojas, pudriciones de semillas, frutos, pedúnculo, raíz y tizón de brotes e inflorescencias (Slippers et al, 2005;Sandoval-Sánchez et al, 2013;Dugan et al, 2015;Hajlaoui et al, 2015;Netto et al, 2017;Rodríguez-Gálvez et al, 2017).…”
Section: Síntomasunclassified
“…Fabaceae (Linaldeddu et al, 2015), naranjo agrio (Alves et al, 2008), coco (Dugan et al, 2015), mango (Johnson et al, 1992;Marques et al, 2013), papayo (Netto et al, 2014), álamo, sauce (Hashemi & Mohammadi, 2016) guapuruvú (Schizolobium parahyba var. Amazonicum) (Mehl et al, 2014), berenjena (Solanum melongena) (Woodward et al, 2005), níspero (Eriobotrya japonica) (González et al, 2017), yaca (Artocarpus heterophyllus) (Ni et al, 2008), palma (Dypsis lutescens) (Pereira et al, 2015), kenaf (Norhayati et al, 2016), Jatropha (Machado et al, 2014) y varias especies introducidas de árboles forestales, de otros países han facilitado la dispersión de este patógeno (Segura-Contreras et al, 2015).…”
Section: P a L A B R A S C L A V Eunclassified
“…It has also been reported that species of Lasiodiplodia are common in the tropics, causing diseases in plants, in pre and post-harvest and that their cellulolytic activity allows for penetration and colonization of the plant in a similar way to those of a soft rot causing-fungus, using the starch and other saccharides present in the initial substrate of the wood (Muñoz et al, 2015). The imports of other fruit hosts of this pathogen from other countries such as the nut and the English walnut (Li et al, 1995), grape (Linaldeddu et al, 2015;Rodríguez et al, 2015), sweet orange, oak, retama: Fabaceae (Linaldeddu et al, 2015), bitter orange (Alves et al, 2008), coconut (Dugan et al, 2015), mango (Johnson et al, 1992;Marques et al, 2013), papaya (Netto et al, 2014), poplar, willow (Hashemi & Mohammadi, 2016) Brazilian firetree (Schizolobium parahyba var. Amazonicum) (Mehl et al, 2014), eggplant (Solanum melongena) (Woodward et al, 2005), loquat (Eriobotrya japonica) (González et al, 2017), jackfruit (Artocarpus heterophyllus) (Ni et al, 2008), golden cane palm (Dypsis lutescens) (Pereira et al, 2015), kenaf (Norhayati et al, 2016), Jatropha (Machado et al, 2014) and various introduced species of forest trees from other countries have eased the dispersion of this pathogen (Segura-Contreras et al, 2015).…”
Section: P a L A B R A S C L A V Ementioning
confidence: 99%